2010
DOI: 10.3174/ajnr.a2026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CT Perfusion in the Setting of Cerebral Ischemia: Patterns and Pitfalls

Abstract: SUMMARY: CTP has a growing role in evaluating stroke. It can be performed immediately following NCCT and has advantages of accessibility and speed. Differentiation of salvageable ischemic penumbra from unsalvageable core infarct may help identify patients most likely to benefit from thrombectomy or thrombolysis. Still, CTP interpretation can be complex. We review normal and ischemic perfusion patterns followed by an illustrative series of technical/diagnostic challenges of CTP interpretation in the setting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 64 publications
0
85
0
6
Order By: Relevance
“…CTP studies show that there is a high rate of intracerebral perfusion deficits that occur without subsequent ischemic lesions in the follow-up MRI. 11,[23][24][25] In ≤20% of patients without cerebral infarction, time-related maps, such as MMT and time to peak, showed a perfusion deficit, whereas CBF showed a perfusion deficit in 5% of the patients without infarction. 11 Our results indicate that infratentorial perfusion deficits, which sometimes are regarded as false-positive, can actually have a pathophysiologic background.…”
Section: May 2014mentioning
confidence: 99%
“…CTP studies show that there is a high rate of intracerebral perfusion deficits that occur without subsequent ischemic lesions in the follow-up MRI. 11,[23][24][25] In ≤20% of patients without cerebral infarction, time-related maps, such as MMT and time to peak, showed a perfusion deficit, whereas CBF showed a perfusion deficit in 5% of the patients without infarction. 11 Our results indicate that infratentorial perfusion deficits, which sometimes are regarded as false-positive, can actually have a pathophysiologic background.…”
Section: May 2014mentioning
confidence: 99%
“…[4][5][6] Additional known pitfalls of CTP analysis include incorrect placement of the perfusion volume, incorrect selection and variability of the AIF and VOF, chance of missing small infarcts due to the low resolution of CTP analysis, and changes in perfusion due to extracranial and intracranial stenosis. 7 On the other hand, it has recently been shown that despite the general belief, the order of scanning (CTA before or after CTP) has no significant influence on quantitative CTP parameters. 8 Although commercial software packages for CTP analysis are widely available, there is currently no standardized method for the analysis.…”
mentioning
confidence: 99%
“…Previous cerebrovascular incidents may form internal weak spots which may converge with external circumstances (evacuation/pressure relief) resulting in a massive intracerbral bleeding and death [5,10]. Therefore, perfusion CT may be necessary before evacuating a large subdural hematoma to differentiate salvageable ischemic penumbra from unsalvageable infarcted brain tissue under the hematoma [18]. This may help identify patients most likely to benefit from hematoma evacuation and decrease the risk of secondary inctracerebral bleeding.…”
Section: Discussionmentioning
confidence: 99%